PENGARUH PENGGUNAAN TANAH GAMBUT SEBAGAI LAHAN PERTANIAN TERHADAP PERUBAHAN POLA LAJU MINERALISASI NITROGEN - Suhardi Suhardi (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2005)
The objective of this research was to determine the change of peat nitrogen mineralization rate under influence of peat land transformation on land culture. Four types of peat land transformation were used in this study. They were : low intensive paddy field (STI), high intensive paddy field (SI), dry land crop (LKS), and palm oil plantation (LKT). Four parameters were used to measure the rate of nitrogen mineralized for this necessity : cumulative of nitrate mineralized (Nt), nitrogen mineraliztion potential (N0), half time of mineralization (Tc), and nitrogen mineralization coefficient (K). This research was carried out in laboratory by incubating followed by leaching the peat by using Stanford and Smith (1972) method. The research revealed that the highest intensity of nitrogen mineralization was reached during first to fourth weeks of incubation. On the other hand, the transformation of peat land to culture land enhanced the rate of nitrogen mineralized which was showed by decrease the value of N0 and Tc, while its K value increased. This research showed that control (undistubed peat land) had the highest value of N0 and Tc (44,094 me NO3 100 g-1 peat and 20,586 weeks) and the lowet K value (0,033 week-1); while the lowest of N0 and Tc values and the highest of K value was obtained by peat land that was transformed to dryland crop (GB7).